Haben Krankenhäuser die Pflicht, die sekundäre Forschungsnutzung von Behandlungsdaten zu unterstützen? - Jungkunz, Martin; Winkler, Eva C.; Schickhardt, Christoph (Ethik in der Medizin, 2024)
Research question The secondary research use of treatment data has the potential to expand medical knowledge and improve patient care. Hospitals play an important role in systematic secondary research use: they generate large amounts of treatment data and are supposed to establish the necessary structures for their use in research. This raises the ethical question: do hospitals have a moral duty to support secondary research use of treatment data by establishing and operating the necessary resources and infrastructure? Procedure Our aim is to outline a conceptual framework to discuss the question and to propose a ﬁrst normative position. Building on insights from business and organizational ethics, we develop a conceptual framework in which we view hospitals as moral actors. Our normative-ethical analysis is based on a reconstructive stakeholder approach, in which we identify the following general duties of hospitals: orientation towards patient wellbeing; cost efﬁciency; enabling employees to act in accordance with professional ethical standards; supporting public health and research. We examine whether these general duties provide reasons for a speciﬁc duty of hospitals to support secondary research use of treatment data. We discuss potential objections to such a duty arising from other, potentially conﬂicting general duties of hospitals (e.g., data protection), from practice (e.g., costs/resources), or related discourses (data ownership).